The self-esteem of special learners in the regular school - Cordero, Monina Jean B. (2007)
Special needs students have long started being mainstreamed in the Philippines. However, it is unsure how they perceive themselves in the regular school. It is questionable if they have high regard of themselves in different environments while interacting with others. This research investigated the main streamed special learner's self-esteem as measured by Brown and Alexander's Self-Esteem Index (SEI) along four domains: Familial Acceptance (FA), Academic Competence (AC), Peer Popularity (PP) and Personality Security (PS). Other factors that could affect self-esteem, such as sex, and parents' educational attainment were also looked into. Fifty-five (55) special learners from various high schools in Quezon City took part in this study. The average Self-Esteem Quotient (SEQ) and the scale's average standard scores were obtained. Regression was used to analyze the relationship between self-esteem and FA, AC, PP and PS. A t-test was used to see whether there was a difference between the SEI scores of female respondents and of male respondents. To examine whether there was a relationship between special learners' self-esteem and their parent's educational attainment, a 1-way analysis of variance test (ANOVA) was utilized. Results showed that special learners have a healthy self-esteem, as shown in average scores in the four domains. It was also found out that sex and parents' educational attainment were not significant factors in the special learners' self-esteem. The study concluded that the higher the score in each of the self-esteem areas, the higher the self-esteem. Recommendations were directed to keeping special learners from being at risk of failure in the regular class and from dropping out of school. Considerations for future research included the development of Filipino self-esteem assessment tools and an assessment of regular class placement for students with special needs.
"October 2007."
Thesis (M.A. Education : Special Education)--University of the Philippines Diliman.
Keywords: Self-esteem in adolescence -- Philippines -- Quezon City; Self-esteem in adolescence -- Study and teaching (Secondary) -- Philippines -- Quezon City; Children with disabilities -- Education (Secondary) -- Philippines -- Quezon City; Special education -- Philippines -- Quezon City